Emotional Intelligence, Self-Efficacy, and Clinical Decision-Making of Perioperative Nurses - Elza Feronika A’yunil Hofi; Tri Anjaswarni; Joko Wiyono; Rudi Hamarno; Duong Thi To Anh (Journal Of Nursing Practice, 2026)
Background: Clinical decision-making is an important aspect of perioperative practice because it determines patient safety and quality of care. Current phenomena show that nurses are still not sensitive to the complexity of patients' emotions, so that emotional aspects are not fully integrated into treatment considerations. Emotional intelligence helps nurses understand and manage their own emotions and those of their patients so that they can assess situations more accurately, while self-efficacy strengthens their confidence in choosing and implementing the right actions. These two factors contribute to the accuracy and consistency of clinical decision-making. Purpose: The purpose of this study was to analyze the relationship between emotional intelligence and self-efficacy with the clinical decision-making of perioperative nurses. Methods: The research method was observational with a cross-sectional approach. The sample was taken using total sampling and consisted of 31 perioperative nurses at a hospital in Batu City. Data analysis used Spearman's rank correlation test and ordinal logistic regression test. Results: The bivariate test results showed a significant relationship between emotional intelligence (p-value = 0.002; r = 0.536) and self-efficacy (p-value = < 0.001; r = 0.568) with the clinical decision-making of perioperative nurses. The correlation coefficient showed a moderate positive correlation, indicating that the higher the emotional intelligence and self-efficacy, the higher the clinical decision-making of perioperative nurses. In the multivariate test, both variables simultaneously had a significant effect on clinical decision-making (p-value = 0.002 < α 0.05). Conclusion: The results of this study contribute significantly to maintaining the quality of nursing services and care provided by nurses through the improvement of emotional intelligence and self-efficacy.